Talent Identification in Youth Soccer: Prognosis of U17 Soccer Performance on the Basis of General Athleticism and Talent Promotion Interventions in Second-Grade Children - Hohmann, Andreas; Siener, Maximilian (Frontiers in Sports and Active Living, 2021)
Several talent identification programs in elementary school have implemented motor diagnostics to introduce children to groups of sports, like game sports, or even to particular sports like soccer. However, as in most other sports, in youth soccer the predictive value of such early testing is still unclear. This prospective study evaluated the mid-term prognostic validity of generic motor performance tests. The sample consisted of male U9 second grade children, and having received a recommendation to participate in soccer. The talent screening campaign was a basic check comprising two anthropometric parameters, five physical fitness and three motor competence diagnostics of the German Motor Test 6-18 (Boes and Schlenker, 2016). The test data were collected from the participating elementary school classes of the years 2010 to 2014. The soccer competition performance of those children who chose the sport soccer (n = 502) up to the end of the season 2019/20 (2020, Sept 30th) was recorded. This group of U17 players was then assigned individually to six different competition levels. The prognostic validity of the physical and physiological tests was determined using ANOVAs, odds ratios, as well as a regression path analysis. All diagnostic methods exhibited medium to high prognostic validity over the eight years time span from the talent screening to the later soccer competitions in the adolescent age groups. For future success in soccer explosive power and motor coordination were of particular importance.